Preparation method of PA6 composite material with low water absorption rate and high strength

The shortcomings of existing PA6 composite materials in flame retardant and water absorption are solved by adding specific components such as adamantane to modify hyperbranched polymers and epoxy domantane to the PA6 composite materials, and melt blending and injection molding, the shortcomings of existing PA6 composite materials in terms of flame retardant effect and water absorption are solved. , PA6 composite material with low water absorption, high strength and good flame retardant properties is achieved.

CN119432055AInactive Publication Date: 2025-02-14XIAMEN JINMU IND CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411787438.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing PA6 composite materials have shortcomings in flame retardant effects and have high water absorption, which affects its mechanical properties.

Method used

By melting and blending materials such as PA6, silicone powder, adamantane, hyperbranched polymer, epoxy dosantane, polyethylene resin, polypropylene, antioxidant 1076 and other materials in a twin-screw extruder, and injection molding with an injection molding machine Forming, a PA6 composite material with low water absorption and high strength was prepared.

Benefits of technology

Low water absorption and high flame retardant properties are achieved while improving the mechanical properties of the material, including tensile strength and bending strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005174422720000071
    Figure BDA0005174422720000071
  • Figure BDA0005174422720000081
    Figure BDA0005174422720000081
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, and discloses a preparation method of a low-water-absorption and high-strength PA6 composite material, which comprises the following steps: adding PA6, silicone powder, an adamantane modified hyperbranched polymer, epoxy adamantane, polyethylene resin, polypropylene and an antioxidant 1076 into a twin-screw extruder, melting, blending and extruding to obtain the low-water-absorption and high-strength PA6 composite material. And carrying out injection molding by using an injection molding machine to prepare the low-water-absorption high-strength PA6 composite material. In the melt blending process, a terminal hydroxyl group in the adamantane modified hyperbranched polymer and an epoxy group in epoxy adamantane are subjected to a ring-opening reaction, cross-linking is generated between the terminal hydroxyl group and the epoxy group, the terminal hydroxyl group and the epoxy group are wound with PA6, and the terminal hydroxyl group and the epoxy group are tightly connected with each other, so that the tensile strength and the bending strength of the material are remarkably improved. Adamantyl groups in the adamantane modified hyperbranched polymer and the epoxy adamantane have good hydrophobicity, and the adamantane modified hyperbranched polymer, the epoxy adamantane, the polyethylene resin and the polypropylene low-water-absorption resin jointly form a low-water-absorption system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a method for preparing a PA6 composite material with low water absorption and high strength. Background Art

[0002] PA6, full name of polyamide 6 or nylon 6, is a polymer compound, a member of the nylon family, with good mechanical strength, wear resistance and chemical stability, and is widely used in the automotive industry, aerospace, electronics and electrical, mechanical building materials, home appliances and textiles, etc. For example, patent CN116162347A discloses a low-water absorption, high-strength and super-tough nylon 6 composite material and its preparation method. The composite material of the invention is composed of a third component of low-water absorption resin dispersed in a second component of toughening resin, forming a masterbatch M to modify the nylon 6 general resin, greatly improve the toughness and rigidity of the nylon 6 resin, and reduce the water absorption rate of the nylon 6 resin, but its flame retardant effect is not improved. Summary of the invention

[0003] 1. Technical issues to be solved

[0004] In view of the deficiencies in the prior art, the present invention provides a method for preparing a PA6 composite material with low water absorption and high strength, which has low water absorption and good flame retardant and mechanical properties.

[0005] (II) Technical solution

[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing a PA6 composite material with low water absorption and high strength, wherein the method for preparing the PA6 composite material with low water absorption and high strength is:

[0007] (1) adding 10-15 parts by weight of 2,2-dimethylolpropionic acid and 30-50 parts by weight of thionyl chloride to a xylene solvent, stirring evenly, heating to 75-90° C., reacting, and then removing the solvent under reduced pressure to obtain an intermediate 1;

[0008] (2) adding 3-hydroxy-1-adamantyl methacrylate to N,N-dimethylamide solvent, stirring and dispersing, adding benzoin dimethyl ether photoinitiator and mercaptoethylamine, irradiating with 365 nm ultraviolet light at 20-40° C. for 2-4 h, centrifuging, washing with deionized water, and drying to obtain amino-modified adamantyl methacrylate;

[0009] (3) adding amino-modified adamantyl methacrylate and intermediate 1 to N,N-dimethylformamide solvent, stirring evenly, and continuously adding triethylamine catalyst thereto, reacting at 70-95° C. for 5-9 hours, and then distilling under reduced pressure, washing and drying to obtain intermediate 2;

[0010] (4) dissolving 8-14 parts by weight of suberic acid and 10-16 parts by weight of intermediate 2 in an acetone solvent, then adding 0.4-0.6 parts by weight of 4-dimethylaminopyridine and 0.2-0.3 parts by weight of N,N-dicyclohexylcarbodiimide, and reacting under reflux at 110-130° C., precipitating, filtering, and washing after the reaction to obtain an adamantane-modified hyperbranched polymer;

[0011] (5) Add dichloromethane solvent, pyridine catalyst, and intermediate 2 to a reaction flask, stir to dissolve, then add 4-vinylbenzoyl chloride, react at room temperature for 5-10 hours, concentrate the solution, wash, and recrystallize to obtain intermediate 3;

[0012] (6) adding the intermediate 3 to N,N-dimethylformamide solvent, stirring evenly, then adding a hydrogen peroxide solution thereto, reacting at 20-30° C. for 2-6 hours, and then distilling under reduced pressure, filtering and drying to obtain epoxyadamantane;

[0013] (7) 60-80 parts by weight of PA6, 1-2 parts by weight of silicone powder, 5-12 parts by weight of adamantane-modified hyperbranched polymer, 6-8 parts by weight of epoxy adamantane, 20-40 parts by weight of polyethylene resin, 25-40 parts by weight of polypropylene, and 0.6-0.8 parts by weight of antioxidant 1076 are added into a twin-screw extruder, melt-blended and extruded, and then injection-molded by an injection molding machine to obtain a PA6 composite material with low water absorption and high strength.

[0014] Preferably, the reaction time in (1) is 4-6 hours.

[0015] Preferably, the mass ratio of 3-hydroxy-1-adamantyl methacrylate, benzoin dimethyl ether photoinitiator and mercaptoethylamine in (2) is 1:0.01-0.03:0.9-1.2.

[0016] Preferably, the mass ratio of amino-modified adamantyl methacrylate, intermediate 1, and triethylamine catalyst in (3) is 1.1-1.3:1:0.02-0.04.

[0017] Preferably, the reflux reaction in (4) is carried out for 15-20 hours.

[0018] Preferably, the mass ratio of the pyridine catalyst to the intermediate 2,4-vinylbenzoyl chloride in (5) is 0.03-0.05:1:1.4-1.8.

[0019] Preferably, the mass ratio of the intermediate 3 to the aqueous hydrogen peroxide solution in (6) is 1:2.1-2.5.

[0020] Preferably, the temperature of melt blending in (7) is 220-240°C.

[0021] (III) Beneficial technical effects

[0022] The invention prepares a PA6 composite material with low water absorption and high strength by adding PA6, silicone powder, adamantane-modified hyperbranched polymer, epoxy adamantane, polyethylene resin, polypropylene and antioxidant 1076 into a twin-screw extruder, melt-blending and extruding, and then injection molding by an injection molding machine.

[0023] The sulfur and nitrogen elements contained in the hyperbranched polymer modified by adamantane and epoxy adamantane have good flame retardant effect. The sulfur element generates strong acidic substances when heated, which can promote the dehydration of the substrate into carbon, and has a good flame retardant effect. The nitrogen element contained therein can generate non-flammable gas when heated, dilute the concentration of flammable gas, and achieve the purpose of flame retardancy. In the process of melt blending, the terminal hydroxyl group in the hyperbranched polymer modified by adamantane will undergo a ring-opening reaction with the epoxy group in the epoxy adamantane, cross-linking will occur between them, and entanglement with PA6 will occur, and they will be closely connected with each other, which significantly improves the tensile strength and bending strength of the material. The hyperbranched polymer contained therein enhances the toughness of the material, and the adamantane contained therein has good mechanical properties. The adamantane group in the hyperbranched polymer modified by adamantane and epoxy adamantane has good hydrophobicity and together with the polyethylene resin and the polypropylene low water absorption resin constitutes a low water absorption system. DETAILED DESCRIPTION

[0024] Example 1

[0025] (1) adding 10 parts by weight of 2,2-dihydroxymethylpropionic acid and 30 parts by weight of thionyl chloride to a xylene solvent, stirring evenly, heating to 75° C., reacting for 4 hours, and then removing the solvent by evaporation under reduced pressure to obtain an intermediate 1;

[0026] (2) adding 3-hydroxy-1-adamantyl methacrylate to N,N-dimethylamide solvent, stirring and dispersing, and then adding benzoin dimethyl ether photoinitiator and mercaptoethylamine, wherein the mass ratio of 3-hydroxy-1-adamantyl methacrylate, benzoin dimethyl ether photoinitiator and mercaptoethylamine is 1:0.01:0.9, irradiating with 365 nm ultraviolet light at 20° C. for 2 h, centrifuging, washing with deionized water, and drying to obtain amino-modified adamantyl methacrylate;

[0027] (3) adding amino-modified adamantyl methacrylate and intermediate 1 to N,N-dimethylformamide solvent, stirring evenly, and continuously adding triethylamine catalyst, wherein the mass ratio of amino-modified adamantyl methacrylate, intermediate 1, and triethylamine catalyst is 1.1:1:0.02, reacting at 70° C. for 5 h, and then distilling under reduced pressure after reaction, washing, and drying to obtain intermediate 2;

[0028] (4) dissolving 8 parts by weight of suberic acid and 10 parts by weight of intermediate 2 in an acetone solvent, then adding 0.4 parts by weight of 4-dimethylaminopyridine and 0.2 parts by weight of N,N-dicyclohexylcarbodiimide, and reacting under reflux at 110° C. for 15 h. After the reaction, precipitating, filtering, and washing to obtain an adamantane-modified hyperbranched polymer;

[0029] (5) Add dichloromethane solvent, pyridine catalyst, and intermediate 2 to a reaction flask, stir and dissolve, then add 4-vinylbenzoyl chloride, wherein the mass ratio of pyridine catalyst, intermediate 2, and 4-vinylbenzoyl chloride is 0.03:1:1.4, react at room temperature for 5 hours, concentrate the solution, wash, and recrystallize to obtain intermediate 3;

[0030] (6) adding the intermediate 3 to N,N-dimethylformamide solvent, stirring evenly, and then adding a hydrogen peroxide aqueous solution, wherein the mass ratio of the intermediate 3 to the hydrogen peroxide aqueous solution is 1:2.1, reacting at 20° C. for 2 h, and then distilling under reduced pressure, filtering and drying to obtain epoxyadamantane;

[0031] (7) 60 parts by weight of PA6, 1 part by weight of silicone powder, 5 parts by weight of adamantane-modified hyperbranched polymer, 6 parts by weight of epoxy adamantane, 20 parts by weight of polyethylene resin, 25 parts by weight of polypropylene, and 0.6 parts by weight of antioxidant 1076 were added into a twin-screw extruder, melt-blended and extruded at 220° C., and then injection-molded using an injection molding machine to obtain a PA6 composite material with low water absorption and high strength.

[0032] Example 2

[0033] (1) 15 parts by weight of 2,2-dimethylolpropionic acid and 50 parts by weight of thionyl chloride were added to a xylene solvent, stirred evenly, heated to 90° C., and reacted for 6 hours. After the reaction, the solvent was removed by evaporation under reduced pressure to obtain an intermediate 1;

[0034] (2) adding 3-hydroxy-1-adamantyl methacrylate to N,N-dimethylamide solvent, stirring and dispersing, and then adding benzoin dimethyl ether photoinitiator and mercaptoethylamine, wherein the mass ratio of 3-hydroxy-1-adamantyl methacrylate, benzoin dimethyl ether photoinitiator and mercaptoethylamine is 1:0.03:1.2, irradiating with 365 nm ultraviolet light at 40° C. for 4 h, centrifuging, washing with deionized water, and drying to obtain amino-modified adamantyl methacrylate;

[0035] (3) adding amino-modified adamantyl methacrylate and intermediate 1 to N,N-dimethylformamide solvent, stirring evenly, and continuously adding triethylamine catalyst, wherein the mass ratio of amino-modified adamantyl methacrylate, intermediate 1, and triethylamine catalyst is 1.3:1:0.04, reacting at 95° C. for 9 h, and then distilling under reduced pressure, washing, and drying to obtain intermediate 2;

[0036] (4) dissolving 14 parts by weight of suberic acid and 16 parts by weight of intermediate 2 in an acetone solvent, then adding 0.6 parts by weight of 4-dimethylaminopyridine and 0.3 parts by weight of N,N-dicyclohexylcarbodiimide, and reacting under reflux at 130° C. for 20 hours. After the reaction, precipitating, filtering, and washing to obtain an adamantane-modified hyperbranched polymer;

[0037] (5) Add dichloromethane solvent, pyridine catalyst, and intermediate 2 to a reaction flask, stir and dissolve, then add 4-vinylbenzoyl chloride, wherein the mass ratio of pyridine catalyst, intermediate 2, and 4-vinylbenzoyl chloride is 0.05:1:1.8, react at room temperature for 10 hours, concentrate the solution, wash, and recrystallize to obtain intermediate 3;

[0038] (6) adding the intermediate 3 to N,N-dimethylformamide solvent, stirring evenly, and then adding a hydrogen peroxide aqueous solution, wherein the mass ratio of the intermediate 3 to the hydrogen peroxide aqueous solution is 1:2.5, reacting at 30° C. for 6 h, and then distilling under reduced pressure, filtering and drying to obtain epoxyadamantane;

[0039] (7) 80 parts by weight of PA6, 2 parts by weight of silicone powder, 12 parts by weight of adamantane-modified hyperbranched polymer, 8 parts by weight of epoxy adamantane, 40 parts by weight of polyethylene resin, 40 parts by weight of polypropylene, and 0.8 parts by weight of antioxidant 1076 were added into a twin-screw extruder, melt-blended and extruded at 240° C., and then injection-molded using an injection molding machine to obtain a PA6 composite material with low water absorption and high strength.

[0040] Example 3

[0041] (1) 12.5 parts by weight of 2,2-dimethylolpropionic acid and 40 parts by weight of thionyl chloride were added to a xylene solvent, stirred evenly, heated to 82° C., and reacted for 5 hours. After the reaction, the solvent was removed by evaporation under reduced pressure to obtain an intermediate 1;

[0042] (2) adding 3-hydroxy-1-adamantyl methacrylate to N,N-dimethylamide solvent, stirring and dispersing, and then adding benzoin dimethyl ether photoinitiator and mercaptoethylamine, wherein the mass ratio of 3-hydroxy-1-adamantyl methacrylate, benzoin dimethyl ether photoinitiator and mercaptoethylamine is 1:0.02:1.1, irradiating with 365 nm ultraviolet light at 30° C. for 3 h, centrifuging, washing with deionized water, and drying to obtain amino-modified adamantyl methacrylate;

[0043] (3) adding amino-modified adamantyl methacrylate and intermediate 1 to N,N-dimethylformamide solvent, stirring evenly, and continuously adding triethylamine catalyst thereto, wherein the mass ratio of amino-modified adamantyl methacrylate, intermediate 1, and triethylamine catalyst is 1.2:1:0.03, reacting at 85° C. for 7 h, and then distilling under reduced pressure, washing, and drying to obtain intermediate 2;

[0044] (4) dissolving 10 parts by weight of suberic acid and 13 parts by weight of intermediate 2 in an acetone solvent, then adding 0.5 parts by weight of 4-dimethylaminopyridine and 0.25 parts by weight of N,N-dicyclohexylcarbodiimide, and reacting under reflux at 120° C. for 18 h. After the reaction, precipitating, filtering, and washing to obtain an adamantane-modified hyperbranched polymer;

[0045] (5) Add dichloromethane solvent, pyridine catalyst, and intermediate 2 to a reaction flask, stir and dissolve, then add 4-vinylbenzoyl chloride, wherein the mass ratio of pyridine catalyst, intermediate 2, and 4-vinylbenzoyl chloride is 0.04:1:1.6, react at room temperature for 8 hours, concentrate the solution, wash, and recrystallize to obtain intermediate 3;

[0046] (6) adding the intermediate 3 to N,N-dimethylformamide solvent, stirring evenly, and then adding a hydrogen peroxide aqueous solution, wherein the mass ratio of the intermediate 3 to the hydrogen peroxide aqueous solution is 1:2.3, reacting at 25° C. for 4 h, and then distilling under reduced pressure, filtering and drying to obtain epoxyadamantane;

[0047] (7) 70 parts by weight of PA6, 1.5 parts by weight of silicone powder, 10 parts by weight of adamantane-modified hyperbranched polymer, 7 parts by weight of epoxy adamantane, 30 parts by weight of polyethylene resin, 32 parts by weight of polypropylene, and 0.7 parts by weight of antioxidant 1076 were added into a twin-screw extruder, melt-blended and extruded at 230° C., and then injection-molded using an injection molding machine to obtain a PA6 composite material with low water absorption and high strength.

[0048] Comparative Example 1

[0049] This comparative example is different from Example 3 in that no adamantane-modified hyperbranched polymer is added.

[0050] Comparative Example 2

[0051] This comparative example is compared with Example 3, except that epoxyadamantane is not added.

[0052] Water absorption (equilibrium 50% RH; 23°C): tested according to ISO 62; Tensile strength (50 mm / min): tested according to ASTM / D638; Flexural strength (1.3 mm / min; 50 mm span): tested according to ASTM / D790.

[0053] Table 1: Water absorption and mechanical properties tests.

[0054] project Water absorption (%) Tensile strength(Mpa) Bending strength(Mpa) Example 1 0.13 103 126 Example 2 0.11 105 128 Example 3 0.12 102 120 Comparative Example 1 0.34 53 82 Comparative Example 2 0.36 50 81

[0055] It can be seen from Table 1 that the PA6 composite materials with low water absorption and high strength prepared by the present invention, Examples 1-3 have lower water absorption and higher mechanical properties than Comparative Examples 1-2.

[0056] The oxygen index of PA6 composite materials was tested with an oxygen index tester, and the combustion grade of PA6 composite materials was tested with a horizontal and vertical combustion tester.

[0057] Table 2: Flame retardancy tests.

[0058]

[0059]

[0060] It can be seen from Table 2 that Examples 1-3 of the present invention have better flame retardant effects than Comparative Examples 1-2.

[0061] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a PA6 composite material with low water absorption and high strength, characterized in that: The preparation method of the PA6 composite material with low water absorption and high strength is as follows: (1) adding 10-15 parts by weight of 2,2-dimethylolpropionic acid and 30-50 parts by weight of thionyl chloride to a xylene solvent, stirring evenly, heating to 75-90° C., reacting, and then removing the solvent under reduced pressure to obtain an intermediate 1; (2) adding 3-hydroxy-1-adamantyl methacrylate to N,N-dimethylamide solvent, stirring and dispersing, adding benzoin dimethyl ether photoinitiator and mercaptoethylamine, irradiating with 365 nm ultraviolet light at 20-40° C. for 2-4 h, centrifuging, washing with deionized water, and drying to obtain amino-modified adamantyl methacrylate; (3) adding amino-modified adamantyl methacrylate and intermediate 1 to N,N-dimethylformamide solvent, stirring evenly, and continuously adding triethylamine catalyst thereto, reacting at 70-95° C. for 5-9 hours, and then distilling under reduced pressure, washing and drying to obtain intermediate 2; (4) dissolving 8-14 parts by weight of suberic acid and 10-16 parts by weight of intermediate 2 in an acetone solvent, then adding 0.4-0.6 parts by weight of 4-dimethylaminopyridine and 0.2-0.3 parts by weight of N,N-dicyclohexylcarbodiimide, and reacting under reflux at 110-130° C., precipitating, filtering, and washing after the reaction to obtain an adamantane-modified hyperbranched polymer; (5) Add dichloromethane solvent, pyridine catalyst, and intermediate 2 to a reaction flask, stir to dissolve, then add 4-vinylbenzoyl chloride, react at room temperature for 5-10 hours, concentrate the solution, wash, and recrystallize to obtain intermediate 3; (6) adding the intermediate 3 to N,N-dimethylformamide solvent, stirring evenly, then adding a hydrogen peroxide solution thereto, reacting at 20-30° C. for 2-6 hours, and then distilling under reduced pressure, filtering and drying to obtain epoxyadamantane; (7) 60-80 parts by weight of PA6, 1-2 parts by weight of silicone powder, 5-12 parts by weight of adamantane-modified hyperbranched polymer, 6-8 parts by weight of epoxy adamantane, 20-40 parts by weight of polyethylene resin, 25-40 parts by weight of polypropylene, and 0.6-0.8 parts by weight of antioxidant 1076 are added into a twin-screw extruder, melt-blended and extruded, and then injection-molded by an injection molding machine to obtain a PA6 composite material with low water absorption and high strength.

2. The method for preparing the PA6 composite material with low water absorption and high strength according to claim 1, characterized in that: The reaction time in (1) is 4-6 hours.

3. The method for preparing the PA6 composite material with low water absorption and high strength according to claim 1, characterized in that: The mass ratio of 3-hydroxy-1-adamantyl methacrylate, benzoin dimethyl ether photoinitiator and mercaptoethylamine in (2) is 1:0.01-0.03:0.9-1.

2.

4. The method for preparing the PA6 composite material with low water absorption and high strength according to claim 1, characterized in that: The mass ratio of amino-modified adamantyl methacrylate, intermediate 1 and triethylamine catalyst in (3) is 1.1-1.3:1:0.02-0.

04.

5. The method for preparing the PA6 composite material with low water absorption and high strength according to claim 1, characterized in that: The reflux reaction in (4) is carried out for 15-20 hours.

6. The method for preparing the PA6 composite material with low water absorption and high strength according to claim 1, characterized in that: The mass ratio of the pyridine catalyst to the intermediate 2,4-vinylbenzoyl chloride in (5) is 0.03-0.05:1:1.4-1.

8.

7. The method for preparing the PA6 composite material with low water absorption and high strength according to claim 1, characterized in that: The mass ratio of the intermediate 3 to the aqueous hydrogen peroxide solution in (6) is 1:2.1-2.

5.

8. The method for preparing the PA6 composite material with low water absorption and high strength according to claim 1, characterized in that: The temperature of melt blending in (7) is 220-240°C.

Citation Information

Patent Citations

  • Low-water-absorption high-strength super-tough nylon 6 composite material and preparation method thereof

    CN116162347A